Dimensions and Challenges of E-Government Applications in Bantaeng Regency - Saharuddin, Saharuddin; Irwan, A. Lukman; Nawawi, Juanda (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2022)
This paper aims to examine the Dimensions and Challenges of E-Government Application in Bantaeng Regency and the factors that influence it. This paper uses a descriptive method. Data collection techniques are used by observation, interviews, and documentation then the data obtained in the field will be analyzed with qualitative techniques. The results showed that the application of the digital/electronic dimension of government in information services has not been optimally carried out by the bantaeng district government, while the digital/electronic dimensions of government include ease of use, trust, functional of interaction from the environment, reliability, content, and display of information, and support. Meanwhile, the influencing factors include supporting and inhibiting factors, from supporting aspects, namely leadership, and institutions, while the inhibiting aspects are community culture and lack of socialization in the community